Role of ChatGPT in Enhancing English Language Learning: A Case Study of University Students - Ahmed, Khalid; Akhter, Shamim; Siwok, Siti Rokiah; Tambi, Fatimah; Ahmed Khan, Afaq; Farooqi, Ubaid ur Rahman (Forum for Linguistic Studies, 2025)
Artificial intelligence (AI) enhances language education by offering personalized, inclusive, and accessible learning solutions, directly supporting UNO SDG 4 of ensuring quality education and promoting lifelong learning opportunities for all. This research explores the impact of ChatGPT on enhancing English language skills such as grammar, vocabulary, writing, and comprehensive reading among Virtual University, Pakistan (VU) students. Employing a mixed methods approach, the study collected data via interviews, surveys, and focus group discussions to investigate students’ perceptions, challenges, and engagement with ChatGPT as a language learning aid. A questionnaire survey was conducted among 100 students at Virtual University of Abbottabad. The data was analyzed by using SPSS software to analyze means, standard deviations, percentages, frequencies, and Cronbach’s alpha. The finding reveals that the emergence of AI technologies has transfigured learning patterns and language acquisition and gathers information while also conveniently helping learners in developing their reading, writing, speaking, and listening skills in a short time period. However, the challenges, such as occasional inaccuracies and the absence of human interaction remain. This research aims to complete the gap in the literature by providing empirical data and learning the incorporation of ChatGPT in VU courses, thus advancing the discussion on effective language education. This study’s major goals are to determine how VU students perceive ChatGPT’s influence on their general language proficiency and to look at how ChatGPT affects their vocabulary acquisition.